Revisiting approaches to and considerations for urinalysis and urine culture reflexive testing. (17th February 2022) - Chambliss, Allison B.; Van, Tam T.
Abstract: Urinalysis is considered the world's oldest laboratory test. Today, many laboratories use macroscopic urinalysis as a screening tool to determine when to subject urine samples for a microscopic urinalysis and/or bacterial culture. While reflexive urine microscopy has been practiced for decades, and reflexive urine culture, more recently, evidence-based guidelines regarding optimal reflexive criteria and workflows are lacking. Standard approaches are hindered, in part, by a lack of harmonization of urinalysis and urine culture practices, heterogeneity in patient populations that are studied, and lack of provider adherence to recommended practices. This review summarizes studies that have evaluated the performance of reflexive urine microscopy and reflexive urine culture, particularly in the context of urinary tract infections. It also examines reported clinical outcomes from reflexive urinalysis interventions and their impact on antibiotic stewardship efforts. Finally, it discusses laboratory operational considerations for the implementation of reflexive algorithms.